ENHANCING PUBLIC SERVICE THROUGH COLLABORATIVE EFFORTS: A CASE STUDY OF EAZY PASSPORT SERVICE AT UNIVERSITY HANG TUAH HOSPITAL - Rokhman Fauzi; Koesmoyo Ponco Aji (Polteknik Imigrasi, 2023)
The community service carried out by the Immigration Class I Tanjung Perak Office and the Immigration Polytechnic through the Eazy Passport Service activities at Hang Tuah University Hospital has proven a significant positive impact on the people who use it. In order to analyze the results of this collaboration, the experimental method approach is used as the basis of the research. The results identified included increasing the accessibility of passport services, efficiency of the processing process, increasing public trust in the government, empowering the community, and increasing knowledge about the requirements and procedures for obtaining passports. In addition to the direct benefits, this collaboration also creates opportunities to improve the overall quality of public services. Despite success, the challenges of implementation and ongoing evaluation must still be overcome. These findings encourage the development of similar collaborative approaches across sectors to optimize public services and meet community needs more effectively.